Socioeconomic and behavioral factors of hypertension among Indian tribal population: Evidence from national family health survey 5. - Bodhi Sri Vidya Vennam; Sai Sushma Kuppli; Jayanta Kumar Bora; Soumya Swaroop Sahoo; Chaitanya Gujjarlapudi; Devi Madhavi Bhimarasetty; Ganga Nagamani Nerusu; Sonu Goel (PLoS ONE)
Background All Indian ethnic groups are experiencing an upsurge in the prevalence of hypertension. The objective of the present study was to explore the association between socioeconomic and behavioral factors of hypertension among the tribal population of India. Methods We used the National Family Health Survey (NFHS) round 5 data conducted in 2019-2021. The final sample size was 67263 tribal women and 8441 tribal men aged 15 to 49 years. Chi-square test and the Cochran-Armitage trend test were employed to evaluate the association. Complex samples logistic regression analysis was conducted using clusters and sampling weights. Interstate variation of the prevalence of hypertension by gender was depicted with spatial maps. Results The prevalence of hypertension among tribal women and men was 12% and 16·2%, respectively. All the independent variables were included in the multivariate model as all were significant at p<0.25 in bivariate analysis. Among both tribal women and men increasing age and at-risk waist hip ratio had higher likelihood ratios for hypertension. Among women, urban residence, lower education status, wealth status and consumption of alcohol were found to be significant predictors of hypertension. Among men, usage of smokeless tobacco was strongly associated with hypertension. Conclusion Our study highlights a higher prevalence of hypertension found in older age, smokeless tobacco users, and abdominal obesity risk among the tribal population. There are interstate variations in the prevalence of hypertension among both men and women. These findings help in identifying the risk factors and geographical locations to be prioritized for hypertension prevention and control and in formulating health action plans focused on the tribal population in India. Appropriate intervention approaches need to be adopted to increase hypertension awareness and control practices, specifically focusing on tribals.